Structural Analysis of Reinforced Concrete Shophouses Due to Addition of Load Mini Tower and BTS, Case Study Site Kertopati - Try Nur Hakim Sarip (LPPM NAROTAMA UNIVERSITY, Indonesia, 2021)
The very rapid development of telecommunications in Indonesia has made business actors in the telecommunications sector compete in building telecommunications towers to fill the entire network throughout Indonesia. As a result of the increasing need for telecommunications services, towers and Base Transceiver Stations (BTS) are increasingly relatively close, especially in urban areas, land problems for tower construction are one of the constraints in improving telecommunications networks, so that the construction of towers on buildings ( roof top) is one solution. As a result of this increase, the tower load increases, it can affect the structure of the building under the tower. This paper describes a re-analysis of the building structure due to additional loads on the tower.